Prevention regulatory focus, desired cultural tightness, civic moral disengagement, and emotional reactions to normative daily transgressions: a serial mediation model among adults in Italy - Baldner, Conrad; Pierro, Antonio (Frontiers in Psychology, 2024)
Why do people have positive or indifferent reactions to norm violations? The present research hypothesized that individuals who focus on the avoidance of negative outcomes, for example punishments for rule violations, (i.e., a prevention focus) are hypothesized to also have a desire for rigid and clear norms (i.e., desired cultural tightness) as well as punishments for norm violations.Such norms and punishments narrow accepted behavior and, if clearly communicated, can limit rule violations. Consequently, individuals who desire higher levels of cultural tightness should be less likely to justify poor citizenship behavior (i.e., civic moral disengagement) as this behavior is antithetical to desired cultural tightness. Finally, such individuals should also be more likely to react negatively to norm violations. Data for the present study was conducted in Italy. 1,181 participants were included in the analysis; participation requirements were that they be adults who were residents of Italy. Participants completed self-report measures of the prevention focus, desired cultural tightness, civic moral disengagement, and reactions to general norm violations (e.g., exceeding the speed limit, vandalism). The hypothesized serial mediation model was supported.This model can help explain why individuals can fail to react to "everyday" norm violations, as well societal-level violations (e.g., failing to respect hygienic standards during the COVID pandemic). It also calls on the need to develop mass communication approaches that can influence individuals' prevention focus on a large scale, as this can have downstream effects of reactions to such violations.